Kristus Di Kerajaan Milenium - Agustinus Depparua (STT Bala Keselamatan Palu, 2019)
The emphasis of this topic is to talk about the position of Christ in the Millennial Kingdom, but before discussing about Christ, it helps us advance the perception of what the Millennium. All Christian believe in a millennial kingdom’s just that there are several different concepts regarding time and place of occurrence of the millennial kingdom. In connection with this it is necessary to look at some of the views about the concept of the kingdom millennium.